Pelatihan Pencegahan dan Penanganan Kekerasan Seksual Berbasis Digital Di Pesantren - Fanaqi, Chotijah; Jufri, Muhammad Taher; Rahman, Sani; Al-Ghifari, Fauzan Faiz; Faisal, Reza Gartiwa (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This Community Service Program (PKM) aims to strengthen the capacity of Pesantren Nurul Huda, Cisurupan District, Garut Regency, in preventing and handling sexual violence through the development of a community-based digital reporting system. The program responds to the core problems of partners, including limited understanding of sexual violence, absence of a safe reporting mechanism, and cultural taboos surrounding open discussions of sexual issues within the pesantren environment. Methodology: This program was carried out using an action research approach through five main stages: planning, socialization and training, technology implementation, mentoring and evaluation, and sustainability planning. A participatory communication method was applied by involving pesantren administrators, students, community leaders, and external institutions in the design and implementation of the Sexual Violence Prevention and Handling Information System (SIPEKA). Results: This program successfully enhanced participants’ knowledge, skills, and awareness of sexual violence prevention. SIPEKA has proven to be an effective, fast, secure, and user-friendly digital reporting system. Conclusions: This program effectively addressed partner issues through technological innovation and participatory communication, encouraging the transformation of pesantren into child-friendly and violence-free educational institutions. Limitations: Program implementation was limited by unequal internet access and cultural resistance, which continues to perceive sexual violence as a taboo. Contribution: This PKM Program offers a replicable model for child-protection-based pesantren that integrates religious values, digital literacy, and information technology as tools for social and institutional empowerment.